Theoretical treatment on externally-seeded superradiance from N2+ in femtosecond laser filamentation in low-pressure nitrogen - Wang, Quanjun; Ding, Pengji; Wilkins, Shane G.; Athanasakis-Kaklamanakis, Michail; Zhang, Yuxuan; Liu, Zuoye; Hu, Bitao (Frontiers in Physics, 2023)
We perform a theoretical investigation of a collective emission in tunnel-ionized nitrogen molecules triggered by a coherent seed pulse. A semiclassical theory of superradiance that includes the superradiant temporal profile, characteristic duration, time delay, intensity is achieved. The theoretical predictions of 391-nm forward emission corresponding to the transition between N_2^+(B^2Σ_u^+,ν'=0) and N_2^+(X^2Σ_g^+,ν=0) as a function of nitrogen gas pressure are compared with the recent experimental data [Ding P. Lasing effect in femtosecond filaments in air, Ph.D. thesis, Universit´e Paris-Saclay (2016)]. The good agreement demonstrates that the time-delayed optical amplification inside the molecular nitrogen ions is superradiance.